Development of English Communicative Skills of Home Stay Village to Increase Tourism Potentials of Phru Nai Village Phru Nai Sub-district Ko Yao District Phang-Nga Province: Development of English Communicative Skills of Home Stay Village to Increase Tourism Potentials of Phru Nai Village Phru Nai Sub-district Ko Yao District Phang-Nga Province - Korudomrat, Bunchoo; Posai, Sakchai; Ragkhanto, Suwatsan (RATANABUTH JOURNAL, 2025)
This research article is part of a larger study entitled “Development of English Communicative Skills of Home Stay Village to Increase Tourism Potentials of Phru Nai Village Phru Nai Sub-district Koh Yao District Phang-Nga Province”. The objectives were to: 1) develop the English communication skills of the homestay community to promote tourism; 2) enhance the community’s capacity to use English effectively in tourism contexts; and 3) propose practical strategies for improving English communication as a tool for community-based tourism development. The target group consisted of 50 homestay business owners from 25 households in Ban Pru Nai, selected using purposive sampling. Research instruments included a questionnaire to assess needs and satisfaction regarding English use, and semi-structured interviews with 10 business owners regarding challenges, obstacles, and suggestions for skill development. Quantitative data were analyzed using frequency, percentage, mean, standard deviation, and t-tests, while qualitative data were interpreted using content analysis. Findings revealed that homestay operators expressed a strong need to improve their English communication skills, particularly in listening and speaking, which are critical for interacting with international tourists. The developed innovation effectively addressed these needs. Post-training test scores significantly improved from a pre-test mean score of ( = 32.68, S.D. = 1.82) to a post-test mean score of ( = 41.92, S.D. = 2.12), indicating the effectiveness of the innovation. The study provides a sustainable framework for developing English communication skills in local tourism communities.